Harnessing and supporting consumer involvement in the development and implementation of Models of Care for musculoskeletal health. Issue 3 (June 2016) - Walsh, Louisa; Hill, Sophie; Wluka, Anita E.; Brooks, Peter; Buchbinder, Rachelle; Cahill, Ainslie; Dans, Leonila F.; Lowe, Dianne; Taylor, Michael; Tugwell, Peter
Abstract: Consumer involvement in the design and delivery of their healthcare is an integral strategy to ensure that health services and systems meet consumers' needs. This is also true for the design and delivery of Models of Care. This chapter presents the identified healthcare needs of people with musculoskeletal conditions and focuses on the current systematic review evidence for consumer involvement interventions in musculoskeletal Models of Care across the micro, meso and macro levels of healthcare. This chapter also presents three case studies of consumer involvement in different aspects of healthcare, offers a series of practice points to help translate the systematic review evidence into practice, and also provides direction to available resources, which support the implementation of consumer involvement within Models of Care.